Analisis Strategi Komunikasi Bisnis dalam Meningkatkan Kualitas Audit pada KAP Gideon Adi dan Rekan Surabaya - Fahira, Fianta Elsya; Shofiatul Jannah, Binti (Program Studi Akuntansi Universitas Panca Bhakti, 2025)
This study discusses the role of business communication in improving audit quality at KAP Gideon Adi and Partners Surabaya. Business communication is an important component in the audit process because it serves to ensure the proper flow of information, uniform understanding of instructions, and efficient coordination between auditors and clients. The population in this study includes all auditors working at KAP Gideon Adi dan Rekan Surabaya, while the research sample consists of junior auditors and senior auditors who are internship mentors and are directly involved in the audit process. This study aims to explain how business communication practices are applied in the implementation of audits, the obstacles that arise, and how such communication contributes to improving audit quality. The research method uses a qualitative approach with a case study design. The results show that the implementation of structured business communication through regular meetings, written reports, digital communication media, and formal documentation can accelerate the delivery of audit information, minimize procedural errors, and improve the accuracy of the evidence obtained. In addition, clear and documented business communication helps auditors overcome misinterpretations with clients and improves team coordination.